Impact of social media technology on efficiency in the food and beverage microentrepreneurship sector / Mohamad Azli Razali ... [et al.] - Razali, Mohamad Azli; Rezo, Khairul Hidayat; Mohammed Ghazali, Asmadi; Besar Sa'aid, Hafizah; Anuar, Azyyati (Universiti Teknologi MARA, Kedah, 2024)
This study addresses the burgeoning impact of social media technology on microentrepreneurship in the Malaysian food and beverage sector. Fueled by a significant surge in social media usage, particularly on platforms like WhatsApp, Facebook, and Instagram, the research aims to identify factors influencing technological acceptance among microentrepreneurs and assess the resultant impact on sector efficiency. Employing a mixed-methods approach, encompassing qualitative interviews and quantitative surveys, the study unravels nuanced insights into the complex interplay between technology adoption, social media usage, and microentrepreneurial efficiency. Initial findings highlight the user-friendly nature of social media platforms and their substantial influence on service quality, customer loyalty, and marketing strategies within the industry. The study's implications extend to practical recommendations for optimizing social media integration, fostering digital readiness among microentrepreneurs, and contributing to the broader discourse on technology adoption in specific organizational contexts.